Pemikiran satira dalam novel Melayu (Kuala Lumpur Dewan Bahasa dan Pustaka, 1997)
Satirical aspects in Malay novels.
Includes bibliographical references (p. 301-313) and index.
Keywords: Humor in literature; Malay fiction -- History and criticism